2000
DOI: 10.1038/sj.leu.2401788
|View full text |Cite
|
Sign up to set email alerts
|

Survival time in a population-based consecutive series of adult acute myeloid leukemia – the prognostic impact of karyotype during the time period 1976–1993

Abstract: A consecutive population-based series of 372 adult acute myeloid leukemias, successfully cytogenetically investigated at a single center between 1976 and 1993, is reported. All medical records were reviewed in order to ascertain the prognostic impact of karyotype, divided into three groups; favorable (t(8;21), t(15;17), and inv(16) irrespective of karyotypic complexity; n = 40), poor (der(1;7), inv(3), −5, del(5q), −7, t(9;22), and complex karyotypes including whole or partial losses of chromosomes 5 and/or 7;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…[13][14][15] In fact, the prognostic value of these two chromosome aberration groups was not significantly different among AML patients, 15 but sufficient data for MDS were lacking. The present study demonstrates that the prognosis of patients who carry À5 and del(5q) are significantly different, as OS and LFS of À5 group were shorter than del(5q) patients even if 5q-syndrome patients were excluded from del(5q) patients ( Figure 2 and data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In fact, the prognostic value of these two chromosome aberration groups was not significantly different among AML patients, 15 but sufficient data for MDS were lacking. The present study demonstrates that the prognosis of patients who carry À5 and del(5q) are significantly different, as OS and LFS of À5 group were shorter than del(5q) patients even if 5q-syndrome patients were excluded from del(5q) patients ( Figure 2 and data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Monosomy 7 and del(7q) have been associated with an adverse outcome in AML, [3][4][5][6] suggesting that the critical region(s) in AML may be in the q-arm. [7][8][9][10] In this study, both EFS and OS were significantly worse for children with ALL with a loss involving chromosome 7 than for patients lacking this abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…2 Monosomy 7 or deletion of 7q in these disorders is associated with poor prognosis. [3][4][5][6] It has been hypothesized that there is a tumor suppressor gene (TSG) on chromosome arm 7q that contributes to the pathogenesis of these diseases, and several chromosomal bands have been identified that contain commonly deleted segments, including 7q22 and different nonoverlapping regions in 7q31-q35. [7][8][9][10] However, a putative TSG has not yet been identified on 7q.…”
Section: Introductionmentioning
confidence: 99%
“…The basic demographic, morphologic, cytogenetic and survival data on the present 372 AML and 389 MDS cases have been reported previously. [29][30][31] The diagnoses were based on the morphologic findings present at the time of karyotypic investigation. Survival was calculated from the time of diagnosis of t-MDS/t-AML until date of last follow-up (18 May 2001).…”
mentioning
confidence: 99%